Formulation and Evaluation of Glipizide-loaded Mucoadhesive Microparticle Using Salvia hispanica Seeds Mucilage as Co-polymer - Ojha, Smriti; Tripathi, Stuti; Tripathi, Shivendra Mani; Mishra, Sudhanshu (Current Bioactive Compounds, 2024)
Aim: Chia seed (Salvia hispanica L.) gum is a mucoadhesive, biodegradable polymer with sustained release properties. Objective: The objective of this study was to compare different formulations of glipizide-loaded microparticles using chia seed mucilage and sodium alginate, focusing on sustained release and mucoadhesive properties. Background: The present study aimed to comparatively evaluate various eco-friendly formulations of glipizide-loaded microparticles prepared using chia seed mucilage and sodium alginate. Materials and Methods: Gum was extracted from chia seeds and lyophilized, and preformulation studies were performed according to established protocols. Microparticles were formulated using the ionic gelation method, with sodium alginate as a copolymer and zinc chloride as a cross-linking agent. The prepared microparticles were evaluated using scanning electron microscopy (SEM) for size and particle aggregation, and Fourier Transform infrared spectroscopy (FTIR) for drug-polymer interaction, entrapment efficiency, swelling index, and in vitro drug release. Results: The % yield of chia seed mucilage was 27.35%. The pH of the mucilaginous suspension was 4.67 ± 0.50. The moisture content value was 14.56 % ± 0.50. The values of Carr's index and Hausner's ratio were 22.58 ± 1.89 and 1.38 ± 0.05, respectively. FTIR spectra showed no interaction between pure glipizide and chia seed mucilage, confirming no possible change in glipizide's pharmacology. SEM studies have confirmed the shape of the microparticles to be spherical, with average sizes ranging from 1235.18 ± 8.7 to 1423.25 ± 9.5 μm, and the drug entrapment efficiency ranged from 64.25 ± 2.52 to 81.82 ± 7.56%. The release of glipizide from the microparticles was sustained, and the Higuchi and Korsmeyer-Peppas models were found to be the best-fit kinetic models. Conclusion: The promising copolymer blend of chia seed mucilage and sodium alginate was used for the development of sustained-release dosage forms. A copolymer blend with a ratio of 1:1 produced glipizide-loaded microparticles with sustained release profiles and good mucoadhesive ability, along with a high percentage of drug entrapment efficiency.
Keywords: microparticles